DomeView : a tool for digital planetariums - Silva, Marco (2010)
The content produced for fulldome projection is usually made in a frame (the master) with a format corresponding to a projection of the dome on a plane, commonly the fisheye projection. Due to the distortions involved, looking at the master does not give a clear idea of the final result once projectedon a planetarium dome. The common solution when creating and composing content is to go through an iterative process, making successive projections on a planetarium until the desired result is achieved. However, repeatedaccess to a planetarium is difficult, costly, and time consuming. So there is a need for an application that can provide theuser with a clear notion of the final result in the planetarium. In addition, if the application could be used to show content in a small (single projector) planetarium, like a portable one, its versatility would increase substantially. This paper reports on such an application: Domeview.